تعزيز مشاركة الطلاب في تعليم المفردات ببرنامج وورد وول القائم على الدماغ: دراسة تجريبية في المدرسة الإسلامية الابتدائية تانجيرانج - Nabila, Elsy; Muhbib, Muhbib; Susilawati, Wati; Fudhaili, Achmad (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
This research aims to analyze the response and participation of fifth-grade students at Islamic Elementary School Mazraatul Ulum in Tangerang City in vocabulary learning using the brain-based Wordwall program. The research highlights the problem of low student participation, as their activities are limited to listening and writing down vocabulary without effective collaboration, which negatively affects their understanding and performance. The researchers used the quantitative descriptive approach using pre- and post-questionnaires to collect data. The research sample consisted of 36 students, with the data analyzed using a Likert scale. The results showed a significant improvement in the level of classroom interaction, as the average response increased from 73.81 in the pre-questionnaire to 80.61 in the post-questionnaire. This indicates an increase in student participation after using the program. The results confirmed the effectiveness of Wordwall in improving students' language proficiency and enthusiasm for learning. The research provides recommendations for using innovative teaching methods to enhance the quality of education and classroom interaction, which contributes to solving the challenges of vocabulary learning more effectively.يهدف هذا البحث إلى تحليل استجابة طلبة الصف الخامس في مدرسة مزرعة العلوم الابتدائية الإسلامية بمدينة تانجيرانج ومشاركتهم في تعليم المفردات باستخدام برنامج وورد وول القائم على الدماغ. يبرز البحث مشكلة ضعف مشاركة الطلبة، حيث تقتصر أنشطتهم على الاستماع وتدوين المفردات دون تعاون فعال، مما أثر سلبا على فهمهم وأدائهم. استخدم الباحثون المنهج الكمي الوصفي باستخدام استبيانات قبلية وبعدية لجمع البيانات وتتكون عينة البحث من ٣٦ طالبا، مع تحليل البيانات باستخدام مقياس ليكرت. أظهرت النتائج تحسنا ملحوظا في مستوى التفاعل الصفي، حيث ارتفع متوسط الاستجابة من ٧٣،٨١ في الاستبيان القبلي إلى ٨٠،٦١ في الاستبيان البعدي. يدل ذلك على زيادة مشاركة الطلبة بعد استخدام البرنامج. وأكدت النتائج فعالية برنامج وورد وول في تحسين كفاءة الطلبة اللغوية وحماسهم للتعلم. يقدم البحث توصيات باستخدام وسائل تعليمية مبتكرة لتعزيز جودة التعليم والتفاعل الصفي، ما يسهم في حل تحديات تعليم المفردات بشكل أكثر فاعلية.